STRATEGI PENGEMBANGAN PADA OBJEK WISATA - Syahputra, Ivan; Sudjatno, Sudjatno (Jurnal Kewirausahaan dan Inovasi, 2023)
The purpose of this study was to determine the application of the Development Strategy in Selecta Recreational Parks. The method used in this research is qualitative (descriptive) method. In this study described the internal and external environmental conditions data collected in the analysis to determine the role of tourism development, EFE and IFE analysis, IE Matrix Analysis, and QSPM Matrix in the company. The results of this study indicate that in the analysis of the internal environment the strength in selecta recreational parks is very high, one of which is the variety of diverse products in the recreational park. while in the analysis of high external environment is community support. In the IE matrix the results are in quadrants I and IV, this position is very suitable for companies to grow and build, one of which is the strategy of product development, market and market penetration. On the results of the QSPM matrix for product development get 6.35 points, for market development get 6.15, and market penetration get 5.91. The results here show the product development strategy gets big points, one of the strategies that can be done is to add new vehicles that have a high enough appeal and increase the use of more modern technology.